Pengaruh Pembelajaran Sosial Emosional terhadap Daya Lenting (Resilience) Anak Kelompok B di PAUD Karya Mandiri 2 - Imas Masitoh; Al Aina Al Mardiyah; Rini Anjasari; Lilis Sari Rosidah (Jurnal Ilmu Pendidikan, 2026)
The low resilience of early childhood in the field is often caused by learning processes that have not integrated structured emotional management. This study aims to analyze the effect of implementing Social Emotional Learning (SEL) on enhancing early childhood resilience. Utilizing a quantitative approach with a one-group pretest-posttest quasi-experimental design, this study involved a saturated sample of 20 group B children at PAUD Karya Mandiri 2, Cianjur. Primary data were collected through structured child behavior observation techniques evaluated collaboratively by the researcher, classroom teachers, and parents to reduce measurement bias. The instrument was assessed using an ordinal scale of 1–4 covering the dimensions of emotional regulation, self-efficacy, optimism, problem analysis, interpersonal relationships, and autonomy. The experimental data were normally distributed based on the Shapiro-Wilk test (); thus, the hypothesis testing was conducted using the Paired Samples t-Test. The results of the analysis showed a significant increase in the children's mean resilience score from  during the pretest to  at the posttest, with a value of  and a significance value of . The effect size testing using Cohen's  yielded a value of , indicating that the SEL intervention has an exceptionally large effect magnitude in shifting children's behavior to become more adaptive. The cildren proved to be better able to calm themselves when disappointed, display a resilient attitude, and build positive social interactions. The study's conclusion confirms that structured social-emotional learning is effective in strengthening early childhood resilience; therefore, it is recommended for teachers to consistently integrate SEL modules into daily lesson plans.